A model of the economic benefits of global hepatitis C elimination: an investment case. (October 2020) - Scott, Nick; Kuschel, Christian; Pedrana, Alisa; Schroeder, Sophia; Howell, Jessica; Thompson, Alexander; Wilson, David P; Hellard, Margaret
Summary: Major gains in reducing the burden of hepatitis C are now possible because of the discovery of a cure. The prevention of premature deaths and increased workforce participation among people who are cured are likely to provide substantial indirect economic benefits. We developed an investment case for hepatitis C for the six WHO world regions, which, to our knowledge, is the first to consider both indirect and direct economic benefits in this context. Scaling up of testing and treatment to reach the 2030 WHO hepatitis C elimination targets was estimated to prevent 2·1 million (95% credible interval 1·3–3·2 million) hepatitis C-related deaths and 10 million (4–14 million) new hepatitis C virus infections globally between 2018 and 2030. This elimination strategy was estimated to cost US41·5 billion (33·1–48·7 billion) in testing, treatment, and health care between 2018 and 2030 (23·4 billion more than the status quo scenario of no testing or treatment scale up), with a global average of 885 (654–1189) per disability-adjusted life-year averted at 2030. Compared with the status quo scenario, the elimination scenario generated 46·1 billion (35·9–53·8 billion) in cumulative productivity gains by 2030. These indirect costs made elimination cost-saving by 2027, with a net economic benefit of 22·7 billion (17·1–27·9 billion) by 2030. This model shows that countries might be underestimating the true burden of hepatitis C and will benefit from investing in elimination.